Frequency of Recurrence of Seizures with Intravenous Versus Intramuscular Magnesium Sulphate in Women with Eclampsia: Seizure Recurrence: IV vs IM Magnesium Sulphate in Eclampsia - Irshad, Laraib; Ahmad, Imtiaz; Khakwani, Mehnaz; Khanam, Fozia (Pakistan Journal of Health Sciences, 2026)
Magnesium sulphate is increasingly being utilized in women with eclampsia. But there is still debate on the ideal route of administration. Objectives: To compare the recurrence of seizures between intravenous (IV) and intramuscular (IM) magnesium sulphate (MgSO4) in women with eclampsia. Methods: This open-label, parallel-group, randomized controlled trial was conducted at the Department of OBG, Nishtar Hospital, Multan, from 13th May to 12th November 2025. A total of 200 women aged 18–45 years, admitted with eclampsia, were enrolled after informed consent and demographic data were collected. Women with intracranial bleeding or prior use of anticonvulsants were excluded. Participants were randomly divided to receive either IV (4g IV bolus then 1g/hour infusion) or IM MgSO4 (4g IV+6g IM loading dose, followed by 2.5g IM, 4 hourly). MgSO₄ was continued for 24 hours post-seizure or delivery. The primary outcome was seizure recurrence within 48 hours. Data were analyzed using SPSS version 25.0 with the chi-square test. Results: The mean age was 24.5 ± 4.9 years, and the mean gestational age was 29.0 ± 3.1 weeks. Most participants were ≤25 years (67%), <30 weeks of gestation (60.5%), and obese (64%). Baseline characteristics were comparable across both groups. Seizure recurrence was higher in the IM group (70%) compared to the IV group (30%), with no statistically significant difference (p=0.059). No significant predictors of seizure recurrence were identified after stratification. Conclusions: Although seizure recurrence was high in the intramuscular MgSO4 group, this was not statistically significant. The intramuscular route can be considered an alternative to the intravenous route.